Exploring How Business Analysts Contribute To The Dynamic Capabilities Of Agile Software Development Teams - Ndlela, Mandlakazi (Department of Information Systems, 2021)
Today's organisations are characterised by high competition and a volatile business environment which continues to be a predicament for agile software development managers and practitioners. Software development frameworks that are designed to help organisations respond to these environments include a group of flexible methodologies known as Agile Software Development. However, reliance on mainly software techniques and tools might not be sufficient, hence the need to consider the capabilities of individual team members, particularly those of Business Analysts. Given that agile methodologies do not explicitly advocate the relevance of Business Analyst role, literature reveals ongoing debates regarding the role of Business Analysts in Agile Software Development teams. This can be attributed, in part, to a knowledge gap concerning the manner in which Business Analysts contribute to overall team capabilities, particularly those which are essential in enabling teams to respond to environmental changes. The purpose of this study was to address this gap by investigating how Business Analysts contribute to the Dynamic Capabilities of Agile Software Development teams. Adopting a deductive approach, this study adapted and applied a research model based on the Dynamic Capabilities theory to explore the value of business analysts in agile teams. This study is interpretive and was executed using a qualitative, single case-study research strategy directed at an Agile Software Development team in the financial services industry. Data was collected through face-to-face, semi-structured interviews; a group interview; nonparticipant observation; documentation; and physical artefacts. The thematic analysis technique was used to analyse the data. Findings reveal that there are several factors that allow Business Analysts to contribute to the Dynamic Capabilities of Agile Software Development teams which include: sharing business operations tacit knowledge; promptly sharing insights about requirement changes and assisting team members in completing tasks; as well as actively participating in sprint planning meetings. The findings also showed that Business Analysts experience difficulty in contributing to Dynamic Capabilities when they lack system, industry, and business rules knowledge. This study provides a useful contribution in two ways. Firstly, it proposes a model that can be applied by researchers to help explore ways in which individuals influence team dynamic capabilities. Secondly, this contribution is important for practitioners as it highlights how the knowledge, skills, and behaviours of Business Analysts may support or hinder their ability to contribute to the Dynamic Capabilities of Agile Software Development teams. This study can be used to inform the design of capacity development programmes for individual team members and Business Analysts, and thus help managers to curate teams which will best promote Dynamic Capabilities. Although substantial data was collected, this research was limited, to some extent, by restricted access to classified and confidential documents. It is proposed that future researchers consider applying a multiple case-study strategy to allow for comparative analysis between teams that operate in different contexts.